2013
DOI: 10.1371/journal.pone.0064638
|View full text |Cite|
|
Sign up to set email alerts
|

The Red Flour Beetle as a Model for Bacterial Oral Infections

Abstract: Experimental infection systems are important for studying antagonistic interactions and coevolution between hosts and their pathogens. The red flour beetle Tribolium castaneum and the spore-forming bacterial insect pathogen Bacillus thuringiensis (Bt) are widely used and tractable model organisms. However, they have not been employed yet as an efficient experimental system to study host-pathogen interactions. We used a high throughput oral infection protocol to infect T. castaneum insects with coleopteran spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
112
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 92 publications
(115 citation statements)
references
References 85 publications
2
112
1
Order By: Relevance
“…Depending on the insect population and the applied dietary spore concentration, B. thuringiensis bv. tenebrionis was able to cause considerable mortality in T. castaneum, with up to 100% mortality induced in a laboratory strain, whereas wild-collected populations generally showed higher resistance (13). Furthermore, we previously found that large amounts of spores can be recovered from infected cadavers (13), and in the present study, we investigated the number of spores that needs to be ingested to cause mortality and quantified the reproduction success of B. thuringiensis bv.…”
mentioning
confidence: 74%
See 2 more Smart Citations
“…Depending on the insect population and the applied dietary spore concentration, B. thuringiensis bv. tenebrionis was able to cause considerable mortality in T. castaneum, with up to 100% mortality induced in a laboratory strain, whereas wild-collected populations generally showed higher resistance (13). Furthermore, we previously found that large amounts of spores can be recovered from infected cadavers (13), and in the present study, we investigated the number of spores that needs to be ingested to cause mortality and quantified the reproduction success of B. thuringiensis bv.…”
mentioning
confidence: 74%
“…tenebrionis. Previously, we showed that in this system, the infection process is fast and mortality is rapidly induced in susceptible larvae (usually within the first 24 h after exposure) (13). Depending on the insect population and the applied dietary spore concentration, B. thuringiensis bv.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Pathogen-induced mortality is typically a sigmoidal function that connects a baseline value for no pathogen exposure with doses inflicting maximal mortality, as determined in several laboratory-based studies (Hughes et al, 2004;Milutinović et al, 2013;Vestergaard et al, 1995). In principle, our model can capture any form of dose-dependent mortality by assigning a killing rate σ x to every exposure class x.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the broad database available for other tenebrionid beetles is valuable because T. castaneum is considered as a model organism for the investigation of immune priming [134][135][136]. One advantage of T. castaneum is that oral priming is possible by adding pathogens or a corresponding supernatant directly to the diet [137]. The gut microbiota in T. castaneum plays an important role in immune priming, but a cold shock applied to the parents is required for transgenerational immune priming [138,139].…”
Section: Immune Priming and Transgenerational Immune Primingmentioning
confidence: 99%